Fatigue life of C-FRCM strengthened corroded RC continuous beams under multi-intervention system. (15th June 2022) - Feng, Ran; Chen, Pi-Yu; Wang, Fangying; Xu, Ying; Zhu, Ji-Hua
Abstract: A new fatigue life prediction model for reinforced concrete (RC) beams is proposed. The model was applied to carbon-fabric reinforced cementitious matrix (C-FRCM) strengthened corroded RC beams under the impressed current cathodic protection (ICCP) and structural strengthening (SS) multi-intervention system. The stress development of steel bar in the fatigue process was captured by employing the fracture mechanics and finite element (FE) analysis. The concept of equivalent initial flaw size (EIFS) was also introduced to account for the actual initial micro crack size of steel bar. The feasibility of the model was validated through comparisons of the numerical deflection, the strain of steel bar and fatigue life of RC beams against the test results. The validated model was then used to examine the effects of key parameters including load level, corrosion degree of steel bar and polarization degree of C-FRCM. Furthermore, the results of the parametric study were used to fit S-N curve and analyse the reliability. The high accuracy of the model was shown to be suitable for the fatigue life prediction of ICCP-SS system in long-term service. It was also found that the fatigue life of the corroded RC beams was greatly improved through strengthening with C-FRCM.